2017
DOI: 10.1002/pola.28870
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of functional polyethylene with regularly distributed thioester pendants via ring‐opening metathesis polymerization

Abstract: Four kinds of functional polyethylene carrying thioester pendants were synthesized via ring-opening metathesis polymerization (ROMP) of alkyl cyclopent-3-enecarbothioate catalyzed by a ruthenium-based commercial catalyst and subsequent hydrogenation of the ROMP products (alkyl 5 ethyl, nbutyl, n-octyl, or n-dodecyl). In these polymers the pendant alkyl thioester groups are precisely distributed along the backbone on every five methylene carbons. Chain structure, molecular weight and molecular weight distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…76 Thioester-containing polypentenamers with similar pendant alkyl groups showed higher T g and T m but reduced thermal stability. 77 Our group's entry point to polypentenamers research came from the ROMP of 4-phenylcyclopentene (5) to produce a precision styrenic rubber (P4PCP) or ethylene-styrene (ES) "like" copolymer (H 2 −P4PCP) following hydrogenation ( Figure 6). 51 Here we reemphasize that, due to the 5-carbon phenyl branch spacing, accessing this microstructure through ES copolymerization is not possible.…”
Section: Acs Macro Lettersmentioning
confidence: 99%
See 2 more Smart Citations
“…76 Thioester-containing polypentenamers with similar pendant alkyl groups showed higher T g and T m but reduced thermal stability. 77 Our group's entry point to polypentenamers research came from the ROMP of 4-phenylcyclopentene (5) to produce a precision styrenic rubber (P4PCP) or ethylene-styrene (ES) "like" copolymer (H 2 −P4PCP) following hydrogenation ( Figure 6). 51 Here we reemphasize that, due to the 5-carbon phenyl branch spacing, accessing this microstructure through ES copolymerization is not possible.…”
Section: Acs Macro Lettersmentioning
confidence: 99%
“…With synthetic progress taking large strides, exploration of thermal and physical properties toward potential applications for functionalized polypentenamers is highly needed. Fan and co-workers recently reported a series of homoallylic ester or thioester-substituted CPs where they systematically increased the size of the ester pendant alkyl group. The T g of the resulting polymers was shown to decrease from −26 °C to −65 °C as the ester pendant was increased from methyl to n -octyl . With n -dodecyl pendants and higher, semicrystalline properties arose from the long alkyl chains .…”
Section: Challenges With Admetmentioning
confidence: 99%
See 1 more Smart Citation
“…ROMP of cyclopentene (CP) derivatives has been largely overshadowed due to their low ring strain, [Δ H p ] = ∼23 kJ mol –1 , which reduces polymerization kinetics and limits high conversions due to the thermodynamics of the equilibrium ROMP. However, ROMP of CP and derivatives has received heightened interest within the last several years. Recently, we reported a method to achieve high conversion, targeted molar mass, and low dispersity ( Đ ) PCP by altering the temperature during ROMP . This method, which we termed variable temperature ROMP (VT-ROMP), initiates polymerization at warm temperature and propagates CP to high conversion by cooling after initiation is complete.…”
mentioning
confidence: 99%
“…They showed good thermal properties such as 5% weight loss temperature (T 5 ) in the range 307–301 °C and T g s in the range 65–110 °C due to the introduction of alicyclic and ester groups in the polymer chains, which endow chain rigidity. Song et al [ 64 ] prepared a functional polyethylene carrying thioester pendants via ring-opening metathesis polymerization (ROMP) of alkyl cyclopent-3-enecarbothioate catalyzed by a ruthenium-based catalyst. They investigated the thermal properties of obtained materials and they reported that the thioester groups were decomposed at 300–400 °C to release volatile fragments of the side groups, and decomposition of polymer backbone was initiated at temperature above 400 °C.…”
Section: Resultsmentioning
confidence: 99%